2021
DOI: 10.1177/1120700021989666
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the optimal drainage technique for septic hip arthritis in children

Abstract: Introduction: The hip is one of the most commonly affected joints in paediatric septic arthritis. Drainage can be performed using arthrocentesis (articular needle aspiration), arthroscopy or arthrotomy. The objective of this systematic review was to identify the most effective drainage technique for septic hip arthritis in the paediatric population. Materials and methods: The electronic MEDLINE, EMBASE and Cochrane databases were systematically searched for original articles that reported outcomes of arthrocen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
(122 reference statements)
0
11
0
Order By: Relevance
“…An arthrotomy gives a good overview of the joint and allows a thorough irrigation, but a disadvantage is a larger incision with more scar tissue. The anterior approach is the most mentioned approach for arthrotomy in paediatric septic hip arthritis[ 6 ].…”
Section: Treatment and Follow-upmentioning
confidence: 99%
See 4 more Smart Citations
“…An arthrotomy gives a good overview of the joint and allows a thorough irrigation, but a disadvantage is a larger incision with more scar tissue. The anterior approach is the most mentioned approach for arthrotomy in paediatric septic hip arthritis[ 6 ].…”
Section: Treatment and Follow-upmentioning
confidence: 99%
“…Recent systematic reviews showed a clear overview of the literature on drainage techniques for septic knee and hip arthritis in children[ 5 , 6 ]. It was concluded that knee arthroscopy might have a lower risk of additional drainage procedures as compared to arthrocentesis and arthrotomy in paediatric septic knee arthritis[ 5 ].…”
Section: Treatment and Follow-upmentioning
confidence: 99%
See 3 more Smart Citations